BEYOND DICHOTOMY WITH TAOIST VISIONIN LE GUIN’S THE LEFT HAND OF DARKNESS - Park, Seol Yoanna; Kurnia, Fabiola; Mustofa, Ali (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2023)
The research set out to shed light on balancing awareness, a key Taoist concept that forms the basis of American science fiction author Ursula K. Le Guin's creative works. The balance in Le Guin's work represented the peaceful coexistence of conflicting forces. Le Guin applied Taoist ideas, such as the interdependence of two opposites and non-interference, to convey her concept of balance. The Left Hand of Darkness by Ursula K. Le Guin, published in 1969, served as the primary text for this qualitative study. In The Left Hand of Darkness, the concept of balance was built on transcending the binary split and forging peaceful connections between I and the Other. To reflect her Taoist understanding of the relationship between I and the Other, Le Guin created an androgynous universe in The Left Hand of Darkness and employed the concept of a journey to the alien territory. The results demonstrated that in Le Guin's make-believe world, the protagonists from two different cultural backgrounds completed their trip by bridging the mental division and acquiring Taoist wisdom. The Yin-Yang emblem and the reading of the ancient poem served as metaphors for the peaceful coexistence of dualistic opposites. By transcending dualistic opposites and recognizing a connection between I and the other, Le Guin's worldview, which drew inspiration from Taoism, achieved holistic success.